The animal health components of a biosurveillance system - Tan, Alwyn, author; Salman, Mo, advisor; McCluskey, Brian, committee member; VandeWoude, Susan, committee member (Colorado State University. Libraries, 2023)
Biosurveillance defines a One Health approach of gathering, integrating, interpreting, and communicating information related to health hazards or diseases affecting human, animal, or plant health and their environment to achieve early detection and warning, situational awareness, and better decision making. Animal health surveillance is an important component within biosurveillance systems comprising a continuum of activities from detecting biological threats, to analyzing relevant data, to managing identified threats, and embracing a One Health concept. Despite ongoing health surveillance activities conducted by various stakeholders in different One Health sectors, numerous health crises continue to occur, affecting the health of humans and animals, the livelihoods of people, the economy, their environment, and social harmony. Zoonotic agents caused a large proportion of these health crises, and nations spent large amounts of resources on disease detection and control measures to safeguard the health of their citizens against these agents. This thesis will explore how the animal health community can strengthen biosurveillance in the following sections: 1) the components of a biosurveillance system from an animal health perspective and opportunities for the animal health surveillance community to enhance biosurveillance; 2) a pilot study on the use of air-sampling as a novel method for animal health surveillance; 3) a scoping review on behavioral barriers, enablers, and interventions for animal owners and producers reporting animal diseases to veterinary authorities; and 4) theoretical demonstration of a biosurveillance system.
Keywords: biosurveillance; epidemiology; zoonosis; disease surveillance; animal health; One Health